Squamous Differentiation and Cytokeratin Expression in an Osteosarcoma: A Case Report and Review of the Literature - Lester J. Layfield M.D; Lyska Emerson; Julia R. Crim; Lor Randall (SAGE Publishing, 2008)
Cytokeratin expression has been documented in a variety of sarcomas including synovial sarcomas, epithelioid sarcomas, Ewing's sarcomas and, rarely, osteosarcomas. In osteosarcomas immunohistochemically shown to expression cytokeratins, a component of epithelioid cells is generally present. These epithelioid cytokeratin positive cells raise the possibility of metastatic disease with prognostic and therapeutic implications differing from primary osteosarcoma. The cytokeratin-expressing cells of the cases reported in the literature have not shown definitive squamous differentiation with keratin pearl formation. We report a case of osteosarcoma in which islands of malignant squamous cells were present showing keratin pearl formation and expression of cytokeratins.